Anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel and preparation method and application thereof
By using anisotropic silk fibroin/natural polysaccharide/nanofiber composite hydrogel in tissue-engineered heart valves, the problems of insufficient mechanical properties and degradation rate of existing materials are solved, and higher mechanical strength and cell recognition are achieved. Suitable for heart valve repair.
Patent Information
- Application Number
- CN202211038676.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing tissue-engineered heart valve (TEHV) materials have shortcomings in mechanical properties and degradation rates, and the hydrogel polymer network is usually isotropic, which cannot effectively simulate the anisotropic structure in biological systems, affecting cell proliferation. and differentiation.
Using anisotropic silk fibroin/natural polysaccharide/nanofiber composite hydrogel, the modified polysaccharide and silk fibroin are alternately superimposed in the nanofiber layer, and functional substances such as cell growth factors are combined to form a core-shell nanofiber structure. , improve the mechanical properties and cell recognition of hydrogels.
It has achieved the increase in mechanical strength of the hydrogel and the induction of cell adhesion and proliferation, inhibited osteogenesis and differentiation, and is suitable for the repair of biomedical materials such as heart valves, providing mechanical properties and biocompatibility that are closer to biological systems.
Smart Images

Figure HDA0003819853530000011 
Figure HDA0003819853530000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical engineering, and specifically relates to an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel and a preparation method and application thereof. Background Art
[0002] Tissue-engineered heart valves (TEHVs) are made by mixing autologous seed cells with biodegradable biomaterials (biodegradable polymers) and culturing them in vitro for a period of time before implanting them into the body. With the continuous proliferation of seed cells, the secretion of extracellular matrix (ECM), and the gradual degradation and absorption of biomaterials, a heart valve with normal structure and function is eventually formed. An ideal TEHV not only overcomes the deficiencies of mechanical valves and biological valves, but also has the characteristics of self-growth, repair, remodeling, and non-immunogenicity, so its clinical application has broad prospects. TEHVs can provide an environment in which patient-derived cells can grow and remodel the scaffold to mimic the inherent valve structure.
[0003] The key to constructing TEHV is the scaffold on which the seed cells depend for survival. Natural polysaccharide hydrogels can achieve mechanical properties close to those of soft tissues and good biocompatibility. They have been widely used in the preparation of scaffolds in recent years, but they still need to be strengthened in terms of mechanical properties and degradation rates. In addition, hydrogel polymer networks are usually isotropic, while many biological systems have clear hierarchical structures that are anisotropic at the macroscopic scale, such as heart valves, skin, and articular cartilage. In heart valves, anisotropy plays a vital role in achieving functions such as heart contraction and relaxation, and anisotropic structures have a great influence on cell proliferation, migration, and differentiation.
[0004] A variety of materials, from natural polymers to synthetic polymers, are used to prepare TEHVs to simulate the biomechanics of valves. Methacrylated gelatin (MeGel) is a common hydrogel biomaterial used in tissue engineering because it has adjustable mechanical properties and provides excellent cell adhesion properties. The inventors have previously demonstrated the ability to bioprint heart valves using MeGel hydrogels, but MeGel does not exhibit nonlinear elasticity that is critical to valve biomechanics. In addition, in bone tissue engineering applications, it was found that MeGel may enhance all properties of CAVDs, such as MSC osteogenic differentiation and ECM calcification. Therefore, hydrogels like MeGel need to be further modified or compounded with other materials to reduce the risk of potential calcification or leaflet retraction.
[0005] Silk fibroin is a natural high molecular weight fibrous protein extracted from silk, accounting for about 70% to 80% of silk, and contains 18 kinds of amino acids, of which glycine (Gly), alanine (Ala) and serine (Ser) account for more than 80% of the total composition. Silk fibroin is rich in sources, has good biocompatibility, is non-toxic and non-irritating. At the same time, silk fibroin can be partially biodegraded, and its degradation products themselves not only have no toxic side effects on tissues, but also have a nutritional and repairing effect on skin and periodontal tissues. It is precisely because of the above properties that silk fibroin has been increasingly widely used in the biomedical field and tissue engineering. Since silk fibroin and human skin protein are fibrous proteins and have many similarities in structure, the affinity of silk fibroin and its hydrolyzate to human skin is unmatched by any other natural protein. The stability and strength of pure silk membranes mainly depend on the β-folding structure and intermolecular hydrogen bonds in the membrane, but the content of these two in pure silk membranes is not high, which makes the crystalline area of silk membranes relatively small, and the strength is insufficient in low-humidity and dry environments. Silk membranes are hard and brittle, and the stretchability is very small, which limits their application in some applications. This urgently requires the electrostatic spinning of silk and other polymers to change the weaknesses of single electrospun silk nanofibers and improve their application value. Summary of the invention
[0006] The purpose of the first aspect of the present invention is to provide an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0007] The purpose of the second aspect of the present invention is to provide a method for preparing the anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel of the first aspect.
[0008] The purpose of the third aspect of the present invention is to provide an application of the anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel of the first aspect in the preparation of biomedical materials.
[0009] The fourth aspect of the present invention aims to provide a biomedical material.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] The first aspect of the present invention provides an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel, comprising S1 and S2:
[0012] S1: an anisotropic core-shell nanofiber layer, wherein the shell layer of the anisotropic core-shell nanofiber comprises a mixture M, the core layer of the anisotropic core-shell nanofiber comprises a synthetic polymer, and the mixture M comprises a modified polysaccharide and silk fibroin;
[0013] S2: modified polysaccharide layer; or
[0014] a modified polysaccharide layer comprising a functional substance;
[0015] The modified polysaccharide comprises at least one of a methacryloyl-modified polysaccharide and a methacryloyloxypropyl-modified polysaccharide;
[0016] The synthetic polymer comprises at least one of polycaprolactone, polylactic acid, polyethylene glycol, polybutylene terephthalate-adipate, and poly(lactide-glycol);
[0017] The functional substance comprises at least one of cell growth factors and stem cells.
[0018] Preferably, the S1 and S2 are alternately stacked.
[0019] Preferably, the number of layers of S1 is n, and the number of layers of S2 is n+1 or n-1; further preferably, the number of layers of S1 is n, and the number of layers of S2 is n+1.
[0020] Preferably, n is 2, 3, 4, 5, or 6; further preferably, n is 2, 3, 4, or 5.
[0021] Preferably, the modified polysaccharide comprises a methacryloyl-modified polysaccharide.
[0022] Preferably, the preparation method of the methacryloyl-modified polysaccharide is as follows: polysaccharide is mixed with a monomer containing a methacryloyl group, and reacted to obtain the methacryloyl-modified polysaccharide.
[0023] Preferably, the polysaccharide comprises at least one of gelatin, hyaluronic acid, sodium alginate, carrageenan and dextran; further preferably, the polysaccharide comprises at least one of gelatin, hyaluronic acid and sodium alginate; further preferably, the polysaccharide comprises gelatin.
[0024] Preferably, the mass volume ratio (g:mL) of the polysaccharide to the monomer containing a methacryloyl group is (0.5-15):7.5; further (1-10):7.5.
[0025] Preferably, the methacryloyl group-containing monomer comprises at least one of methacrylic anhydride and glycidyl methacrylate; and further comprises methacrylic anhydride.
[0026] Preferably, the polysaccharide is a polysaccharide solution.
[0027] Preferably, the pH of the polysaccharide solution is 7.5-10; further 8-9.
[0028] Preferably, the concentration of the polysaccharide solution is 0.5-30% by mass volume ratio (w / v, g / mL); more preferably, the concentration of the polysaccharide solution is 1-10% by mass volume ratio (w / v).
[0029] Preferably, the number average molecular weight of the gelatin is 30000D to 100000D; further 30000D to 80000D.
[0030] Preferably, the reaction conditions are: pH = 7.5-10, reaction at 35-45°C for 4-8h; further: pH = 8-9, reaction at 35-40°C for 6-8h.
[0031] Preferably, the reaction further includes dialysis and drying steps.
[0032] Preferably, the molecular weight cut-off in the dialysis is 3000-4000D; further 3000-3500D; further 3500D.
[0033] Preferably, the functional substance comprises stem cells; and further comprises mesenchymal stem cells.
[0034] Preferably, the density of the mesenchymal stem cells in the modified polysaccharide is 10 5 ~10 8 cells / mL modified polysaccharide; further 10 6 ~10 7 cells / mL modified polysaccharide.
[0035] Preferably, the modified polysaccharide comprises at least one of gelatin modified with a methacryloyl group, hyaluronic acid modified with a methacryloyl group, and sodium alginate modified with a methacryloyl group; further preferably, the modified polysaccharide comprises gelatin modified with a methacryloyl group.
[0036] Preferably, the orientation degree of the anisotropic core-shell nanofiber layer is 0.112 to 0.125; further 0.113 to 0.119.
[0037] Preferably, the thickness of the anisotropic core-shell nanofiber layer is 0.1 to 1.3 mm; further 0.1 to 0.5 mm.
[0038] Preferably, the thickness of the modified polysaccharide layer is 3 to 6 mm; further preferably 4 to 5 mm.
[0039] Preferably, the synthetic polymer comprises at least one of polycaprolactone, polylactic acid, polyethylene glycol, and polybutylene terephthalate-adipate; further comprises at least one of polycaprolactone, polylactic acid, and polyethylene glycol; further comprises polycaprolactone, polylactic acid, or polyethylene glycol.
[0040] Preferably, the number average molecular weight of the polycaprolactone is 40000D to 100000D; further, 60000 to 65000D.
[0041] Preferably, the number average molecular weight of the polylactic acid is 10000D to 100000D; further, 40000D to 60000D.
[0042] Preferably, the number average molecular weight of the polyethylene glycol is 1000D to 20000D; further 6000D to 8000D.
[0043] Preferably, the mass ratio of the core layer to the shell layer is 1:(0.5-9.5); further 1:(1-9).
[0044] Preferably, the mass ratio of the silk fibroin to the modified polysaccharide in the mixture M is 1:(0.5-9.5); further 1:(1-9).
[0045] Preferably, the preparation method of the anisotropic core-shell nanofibers is as follows: using a solution of the mixture M as a shell spinning solution and a solution of a synthetic polymer as a core spinning solution, coaxial electrospinning is performed to obtain anisotropic core-shell nanofibers.
[0046] Preferably, the concentration of the solution of the mixture M is 10 to 25 wt %; further 15 to 20 wt %.
[0047] Preferably, the solvent of the solution of the mixture M is a mixture of hexafluoroisopropanol and acetic acid.
[0048] Preferably, the mass ratio of hexafluoroisopropanol to acetic acid is (8-10):1; further 9:1.
[0049] Preferably, the concentration of the acetic acid is 80-95 v / v%; further preferably 90%.
[0050] Preferably, the concentration of the synthetic polymer solution is 5 to 20 wt %; further preferably, 10 to 15 wt %.
[0051] Preferably, the solvent of the synthetic polymer solution is a mixture of hexafluoroisopropanol and acetic acid.
[0052] Preferably, the mass ratio of hexafluoroisopropanol to acetic acid is (8-10):1; further 9:1.
[0053] Preferably, the concentration of the acetic acid is 80-95 v / v%; further preferably 90%.
[0054] Preferably, the steps of coaxial electrospinning are as follows: the shell layer spinning solution and the core layer spinning solution are placed in an injection device respectively, the propulsion speed of the shell layer spinning solution is 0.1-2 mL / h, the propulsion speed ratio of the shell layer spinning solution to the core layer spinning solution is 1:(0.5-1.5), the distance between the needle of the injection device and the receiving device is 8-25 cm, the rotation speed of the receiving device is 500-3500 rpm, and the spinning voltage is 10-30 kV.
[0055] Preferably, the propulsion speed of the shell spinning solution is 0.5-1 mL / h.
[0056] Preferably, the distance between the needle of the injection device and the receiving device is 10-20 cm.
[0057] Preferably, the needle is connected to the positive electrode, and the receiving device is connected to the negative electrode.
[0058] Preferably, the receiving device is coated with tin foil.
[0059] Preferably, the rotation speed of the receiving device is 1000-3000 rpm.
[0060] Preferably, the spinning voltage is 20-22.5 kV.
[0061] The second aspect of the present invention provides a method for preparing the anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel according to the first aspect of the present invention, wherein the preparation method is S11 or S12:
[0062] S11: mixing the modified polysaccharide with a photoinitiator to obtain a mixture A; stacking the mixture A with anisotropic core-shell composite nanofibers, and photocuring to obtain an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel comprising an anisotropic core-shell composite nanofiber layer S1 and a modified polysaccharide layer S2;
[0063] S12: Mix the functional substance, photoinitiator and modified polysaccharide to obtain mixture B; stack the mixture B with anisotropic core-shell composite nanofibers, and photocuring to obtain an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel comprising S1 anisotropic core-shell composite nanofiber layer and S2 modified polysaccharide layer containing functional substances.
[0064] Preferably, the preparation method is S11 or S12:
[0065] S11: mixing the modified polysaccharide with a photoinitiator to obtain a mixture A; alternately stacking the mixture A with anisotropic core-shell composite nanofibers, and photocuring to obtain an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel comprising an S1 anisotropic core-shell composite nanofiber layer and an S2 modified polysaccharide layer;
[0066] S12: Mix the functional substance, photoinitiator and modified polysaccharide to obtain mixture B; alternately stack mixture B and anisotropic core-shell composite nanofibers, and photocuring to obtain an anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel comprising S1 anisotropic core-shell composite nanofiber layer and S2 modified polysaccharide layer containing functional substances.
[0067] Preferably, the concentration of the modified polysaccharide in S11 is 10-20% by mass volume; further 12-15%.
[0068] Preferably, the solvent for the modified polysaccharide in S11 is water.
[0069] Preferably, the photoinitiator comprises an Irgacure series photoinitiator.
[0070] Preferably, the final concentration of the photoinitiator in the mixture A or the mixture B is 0.01 to 0.1% by mass volume; further 0.03 to 0.06%; further 0.03 to 0.05%.
[0071] Preferably, the concentration of the modified polysaccharide in S12 is 8 to 16% by mass volume; further 10 to 15%.
[0072] Preferably, the solvent for the modified polysaccharide in S12 is culture medium; further, DMEM-F12 culture medium.
[0073] Preferably, when the functional substance in S12 is stem cells, the ratio of the functional substance to the mixture of the modified polysaccharide and the photoinitiator is 10: 5 ~10 8 cells / mL mixture; further 10 6 ~10 7 cells / mL mixture.
[0074] Preferably, the light curing method is S111 and / or S112:
[0075] S111: Photocuring under UV light;
[0076] S112: Realized by 3D printer.
[0077] Preferably, the S111 is: photocuring under 360-370nm ultraviolet light for 1-10min; further: photocuring under 365nm ultraviolet light for 5min.
[0078] Preferably, the 3D printer is a 3D printer that adopts the working principle of stereolithography (SLA), preferably a 3D printer of model 3D systems ProX 800.
[0079] The third aspect of the present invention provides the use of the anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel of the first aspect in the preparation of biomedical materials.
[0080] Preferably, the biomedical material is used for tissue repair; further preferably, the biomedical material is used for soft tissue repair; even further preferably, the biomedical material is used for heart valve tissue repair.
[0081] The fourth aspect of the present invention provides a biomedical material comprising the anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel of the first aspect of the present invention.
[0082] Preferably, the biomedical material is used for tissue repair; further preferably, the biomedical material is used for soft tissue repair; even further preferably, the biomedical material is used for heart valve tissue repair.
[0083] The beneficial effects of the present invention are:
[0084] The present invention provides an anisotropic silk protein / natural polysaccharide / nanofiber composite hydrogel, comprising S1 and S2: S1: an anisotropic core-shell nanofiber layer, the shell layer of the anisotropic core-shell nanofiber comprises a mixture M, the core layer of the anisotropic core-shell nanofiber comprises a synthetic polymer, and the mixture M comprises modified polysaccharide and silk protein; S2: a modified polysaccharide layer; or a modified polysaccharide layer comprising a functional substance; the hydrogel is provided with photocuring ability and printability by means of the modified polysaccharide; the anisotropic core-shell nanofiber The hydrogel has good mechanical properties and silk fibroin, and inhibits the osteogenic differentiation of cells. The hydrogel is designed with anisotropic core-shell nanofibers, in which a synthetic polymer with strong mechanical strength serves as the inner core to bear the mechanical support, and a silk fibroin / modified polysaccharide with cell recognition sites and specific proteins serves as the outer shell to be responsible for the adhesion, proliferation and differentiation induction of cells, and has a good interface compatibility with the modified polysaccharide bulk hydrogel. The hydrogel can be used to prepare biomedical materials with tissue (such as vascular forks, heart valves, etc.) repair functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] Figure 1 It is a strain energy data diagram of the acellular hydrogels prepared in Comparative Examples 1 to 3 and Examples 1 to 3 (n=3).
[0086] Figure 2Graphs showing the expression levels of Runx2 gene and osteocalcin OCN gene in HADMSC cells in the cell-laden hydrogels of Examples 4 to 6 and Comparative Examples 4 to 6 (n=3). DETAILED DESCRIPTION
[0087] The present invention is further described in detail below through specific examples.
[0088] It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0089] The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The materials and reagents used in the examples are commercially available unless otherwise specified.
[0090] Example 1 Preparation method of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel
[0091] (1) Preparation of modified gelatin: 10 g of gelatin (Sigma, G9382 derived from cowhide, number average molecular weight 80000D) was weighed and dissolved in 100 mL of ultrapure water to prepare a gelatin solution with a mass volume ratio (g / mL) of 10%, and then the pH was adjusted to 8.5 with a 5 mol / L NaOH solution; 7.5 mL of methacrylic anhydride was added dropwise, and the reaction was carried out at 40° C. for 6 h. During the entire reaction process, the pH of the reaction solution was controlled at 8 to 9 by NaOH; the product obtained by the reaction was dialyzed in a dialysis bag with a molecular weight cutoff of 3500 for 3 days, and freeze-dried to obtain modified gelatin.
[0092] (2) Preparation of anisotropic core-shell composite nanofibers: Polycaprolactone (PCL, Aladdin, CAS No.: 24980-41-4; Mn = 60000-65000D) was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a polycaprolactone (PCL) spinning solution with a concentration of 15 wt%. Modified gelatin (MeGel) and silk fibroin (Aladdin, CAS No. W293432 water-soluble silk fibroin, The mixture was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a 15 wt% SF / MeGel mixed spinning solution, and PCL / SF / MeGel electrospun composite nanofibers with MeGel and SF as shells and polycaprolactone as cores were prepared by coaxial electrospinning technology, as follows: the SF / MeGel mixed spinning solution and PCL were spun The solutions were sucked into a 5mL syringe respectively and then injected into the coaxial needle, wherein the mixed spinning solution was injected into the outer tube of the coaxial needle, and the PCL spinning solution was injected into the inner tube of the coaxial needle. The flow rate (push speed) of the inner and outer tubes was set to 1:1, both of which were 0.5mL / min. The needle was 15cm away from the roller bracket. The tubular bracket composed of composite nanofibers can be prepared by replacing receiving devices with different diameters. Here, the roller diameter is set to 2.0cm for receiving electrospun fibers, and the roller speed is 2000rpm; at high voltage (22.5kV), The spinning solution is sprayed in an electric field to form fibers that are deposited on a receiver to form a fiber membrane; the electrospinning voltage and spinning speed are randomly adjusted according to the spinning conditions, and when the desired thickness is reached (0.1 mm in this case), the aluminum foil and the fiber membrane are carefully peeled off from the roller surface; the morphology of the electrospun fibers is observed using a scanning electron microscope (SEM) and photographed; based on the obtained SEM image, the electrospun fiber scanning electron microscope image is converted into a grayscale image (8-bit, 2048x2048 pixels) 2D-FFT image, and then processed by the image analysis software Image J and its plug-in Ovalprofile, and the orientation degree of the prepared nanofibers is analyzed and calculated, and the orientation degree is 0.116.
[0093] (3) Preparation of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel: The modified gelatin prepared in step (1) was prepared into 50 mL of modified gelatin solution A with a concentration of 12% by weight by volume using ultrapure water; a photoinitiator Irgacure 2959 (CIBA Chemicals) was added to the modified gelatin solution A to obtain solution C, wherein the final concentration of Irgacure 2959 was 0.05% by weight by volume; solution C was compounded with the anisotropic core-shell composite nanofiber prepared in step (2) (the solution C was filled into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and nanofibers were alternately placed during the process, with 3 nanofiber layers, and the upper and lower layers were solution C), and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution C can also be printed by 3D systems ProX 800 and photocured during the printing process), thereby obtaining anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0094] Example 2 Preparation method of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel
[0095] (1) Preparation of modified gelatin: 10 g of gelatin (Sigma, G9382 derived from cowhide, number average molecular weight 80000D) was weighed and dissolved in 100 mL of ultrapure water to prepare a gelatin solution with a mass volume ratio (g / mL) of 10%, and then the pH was adjusted to 8.5 with a 5 mol / L NaOH solution; 7.5 mL of methacrylic anhydride was added dropwise, and the reaction was carried out at 40° C. for 6 h. During the entire reaction process, the pH of the reaction solution was controlled at 8 to 9 by NaOH; the product obtained by the reaction was dialyzed in a dialysis bag with a molecular weight cutoff of 3500 for 3 days, and freeze-dried to obtain modified gelatin.
[0096] (2) Preparation of anisotropic core-shell composite nanofibers: Polyethylene glycol (PEG, Aladdin, CAS No.: 25322-68-3, Product No. P103734, Mn = 8000D) was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a polyethylene glycol (PEG) spinning solution with a concentration of 15 wt %. Modified gelatin (MeGel) and silk fibroin were mixed in a mass ratio of 9:1 to obtain a mixed nanofiber. The mixture was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a 20 wt% SF / MeGel mixed spinning solution. The PEG / SF / MeGel electrospun composite nanofibers with MeGel and SF as shells and polyethylene glycol as cores were prepared by coaxial electrospinning technology. Specifically, the SF / MeGel mixed spinning solution and the PEG spinning solution were respectively sucked into a 5 mL syringe. The device is then injected into the coaxial needle, wherein the mixed spinning solution is injected into the outer tube of the coaxial needle, and the PEG spinning solution is injected into the inner tube of the coaxial needle. The flow rate of the inner and outer tubes is set to 1:1, both of which are 0.5mL / min. The needle is 10cm away from the roller bracket. The tubular bracket composed of composite nanofibers can be prepared by replacing receiving devices with different diameters. Here, the roller diameter is set to 2.0cm for receiving electrospun fibers, and the roller speed is 1000rpm; under the action of high voltage (22.5kV), the spinning solution is in the electric field The fibers are deposited on the receiver by the jet and form a fiber membrane. The electrospinning voltage and spinning speed are randomly adjusted according to the spinning conditions. When the desired thickness is reached (0.2 mm in this case), the aluminum foil and the fiber membrane are carefully peeled off from the roller surface. The morphology of the electrospun fibers is observed under a scanning electron microscope (SEM) and photographed. Based on the obtained SEM image, the SEM image of the electrospun fibers is converted into a grayscale image (8-bit, 2048x2048 pixels) 2D-FFT image, which is then processed by the image analysis software Image J and its plug-in Oval profile to analyze and calculate the orientation degree of the prepared nanofibers, and the orientation degree is 0.113.
[0097] (3) Preparation of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel: The modified gelatin prepared in step (1) was prepared into 50 mL of modified gelatin solution A with a concentration of 15% by mass volume by ultrapure water; a photoinitiator Irgacure 2959 (CIBA Chemicals) was added to the modified gelatin solution A to obtain solution C, wherein the final concentration of Irgacure 2959 was 0.05% by mass volume; solution C was compounded with the anisotropic core-shell composite nanofiber prepared in step (2) (the solution C was filled into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and nanofibers were alternately placed during the process, with 5 nanofiber layers, and the upper and lower layers were solution C), and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution C can also be printed by 3D systems ProX 800 and photocured during the printing process), thereby obtaining anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0098] Example 3 Preparation method of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel
[0099] (1) Preparation of modified gelatin: 10 g of gelatin (Sigma, G9382 derived from cowhide, number average molecular weight 80000D) was weighed and dissolved in 100 mL of ultrapure water to prepare a gelatin solution with a mass volume ratio (g / mL) of 10%, and then the pH was adjusted to 8.5 with a 5 mol / L NaOH solution; 7.5 mL of methacrylic anhydride was added dropwise, and the reaction was carried out at 40° C. for 6 h. During the entire reaction process, the pH of the reaction solution was controlled at 8 to 9 by NaOH; the product obtained by the reaction was dialyzed in a dialysis bag with a molecular weight cutoff of 3500 for 3 days, and freeze-dried to obtain modified gelatin.
[0100] (2) Preparation of anisotropic core-shell composite nanofibers: Polylactic acid (PLA, Aladdin, CAS No.: 26100-51-6, Mn = 60000) was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a 10 wt% polylactic acid (PLA) spinning solution; modified gelatin (MeGel) and silk fibroin were mixed in a mass ratio of 5:5 to obtain a mixture, and the mixture was dissolved in A mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid is 9:1) was used to prepare a SF / MeGel mixed spinning solution with a concentration of 18 wt%. PLA / SF / MeGel electrospun composite nanofibers with MeGel and SF as shells and polylactic acid as cores were prepared by coaxial electrospinning technology. Specifically, the SF / MeGel mixed spinning solution and the PLA spinning solution were sucked into a 5 mL syringe respectively, and then injected into the same The mixed spinning solution is injected into the outer tube of the coaxial needle, and the PEG spinning solution is injected into the inner tube of the coaxial needle. The flow rate of the inner and outer tubes is set to 1:1, both of which are 0.5 mL / min. The needle is 20 cm away from the roller bracket. The tubular bracket composed of composite nanofibers can be prepared by replacing receiving devices with different diameters. Here, the roller diameter is set to 2.0 cm for receiving electrospun fibers, and the roller speed is 3000 rpm. Under the action of high voltage (22.5 kV), the spinning solution is sprayed in the electric field to form fibers deposited on the receiver to form a fiber membrane. The electrospinning voltage and spinning speed are randomly adjusted according to the spinning situation. When the required thickness (0.5 mm in this case) is reached, the aluminum foil and the fiber membrane are carefully peeled off from the roller surface. The morphology of the electrospun fibers is observed and photographed according to a scanning electron microscope (SEM). Based on the obtained SEM image, the electrospun fiber scanning electron microscope image is converted into a grayscale image (8-bit, 2048x2048 pixels) 2D-FFT image, and then analyzed by image analysis software Image J and its plug-in Oval profile were processed and the orientation degree of the prepared nanofibers was analyzed and calculated, and the orientation degree was 0.119.
[0101] (3) Preparation of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel: The modified gelatin prepared in step (1) was prepared into 50 mL of modified gelatin solution A with a concentration of 12% by weight by volume using ultrapure water; a photoinitiator Irgacure 2959 (CIBA Chemicals) was added to the modified gelatin solution A to obtain solution C, wherein the final concentration of Irgacure 2959 was 0.05% by weight by volume; solution C was compounded with the anisotropic core-shell composite nanofiber prepared in step (2) (the solution C was filled into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and nanofibers were alternately placed during the process, with 3 nanofiber layers, and the upper and lower layers were solution C), and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution C can also be printed by 3D systems ProX 800 and photocured during the printing process), thereby obtaining anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0102] Example 4 Preparation method of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells
[0103] The preparation method of this embodiment is the same as that of embodiment 1, except that step (3) is:
[0104] Preparation of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells: sterilize all materials under ultraviolet light for more than 1 hour, dissolve the modified gelatin prepared in step (1) in DMEM-F12 culture medium, and obtain solution B with a modified gelatin concentration of 10% by weight volume; add a photoinitiator Irgacure 2959 (CIBA Chemicals) solution to solution B to obtain solution D, wherein the final concentration of Irgacure 2959 is 0.05% by weight volume; 7 cells / mL of solution D, human adipose-derived mesenchymal stem cells (HADMSC cells, Sigma) were inoculated into solution D to obtain solution E; solution E was injected into the upper and lower layers of a disc mold with a diameter of 8 mm and a thickness of 3 mm, 1 mm each, and the 0.1 mm anisotropic core-shell composite nanofibers prepared in step (2) were added in the middle, and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution E can also be printed by 3D systems ProX 800 and photocured during the printing process), so as to obtain a cell-laden anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0105] Example 5 Preparation method of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells
[0106] The preparation method of this embodiment is the same as that of embodiment 2, except that step (3) is:
[0107] Preparation of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells: sterilize all materials under ultraviolet light for more than 1 hour, dissolve the modified gelatin prepared in step (1) in DMEM-F12 culture medium, and obtain solution B with a modified gelatin concentration of 15% by weight volume; add a photoinitiator Irgacure 2959 (CIBA Chemicals) solution to solution B to obtain solution D, wherein the final concentration of Irgacure 2959 is 0.05% by weight volume; and 7 cells / mL of solution D, human adipose-derived mesenchymal stem cells (HADMSC cells, Sigma) were inoculated into solution D to obtain solution E; solution E was injected into the upper and lower layers of a disc mold with a diameter of 8 mm and a thickness of 3 mm, 1 mm each, and the 0.2 mm anisotropic core-shell composite nanofibers prepared in step (2) were added in the middle, and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution E can also be printed by 3D systems ProX 800 and photocured during the printing process), so as to obtain a cell-laden anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0108] Example 6 Preparation method of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells
[0109] The preparation method of this embodiment is the same as that of embodiment 3, except that step (3) is:
[0110] Preparation of anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells: sterilize all materials under ultraviolet light for more than 1 hour, dissolve the modified gelatin prepared in step (1) in DMEM-F12 culture medium, and obtain a solution B with a modified gelatin concentration of 12% by weight volume; add a photoinitiator Irgacure 2959 (CIBA Chemicals) solution to solution B to obtain a solution D, wherein the final concentration of Irgacure 2959 is 0.05% by weight volume; and 7cells / mL of solution D, human adipose-derived mesenchymal stem cells (HADMSC cells, Sigma) were inoculated into solution D to obtain solution E; solution E was injected into the upper and lower layers of a disc mold with a diameter of 8 mm and a thickness of 3 mm, 1 mm each, and the 0.5 mm anisotropic core-shell composite nanofibers prepared in step (2) were added in the middle, and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution E can also be printed by 3D systems ProX 800 and photocured during the printing process), so as to obtain a cell-laden anisotropic silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0111] Comparative Example 1: Preparation method of a hydrogel
[0112] (1) Preparation of modified gelatin: The preparation method of modified gelatin is the same as that in Example 1.
[0113] (2) Preparation of hydrogel: Modified gelatin was dissolved in deionized water to prepare a modified gelatin solution with a mass volume ratio of 15%, and then a photoinitiator Irgacure 2959 (CIBA Chemicals) solution was added, wherein the final concentration of Irgacure 2959 was 0.05% by mass volume ratio. The modified gelatin solution with the photoinitiator added was injected into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and then placed under 365 nm ultraviolet light for photocuring for 5 minutes to obtain a hydrogel.
[0114] Comparative Example 2 Preparation method of a randomly oriented natural polysaccharide / nanofiber composite hydrogel
[0115] (1) Preparation of modified gelatin: The preparation method of modified gelatin is the same as that in Example 1.
[0116] (2) Preparation of randomly oriented (isotropic) core-shell composite nanofibers without silk fibroin: Polycaprolactone (PCL, Aladdin, CAS No.: 24980-41-4; Mn = 60000-65000D) was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a polycaprolactone (PCL) spinning solution with a concentration of 15 wt%; modified gelatin (MeGel) was added to the mixture. A 15 wt% MeGel spinning solution was prepared in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1). PCL / MeGel electrospun composite nanofibers with MeGel as the shell and polycaprolactone as the core were prepared by coaxial electrospinning technology. The details were as follows: MeGel spinning solution and PCL spinning solution were sucked into a 5 mL syringe respectively, and then injected into the coaxial needle. The silk solution was injected into the outer tube of the coaxial needle, and the PCL spinning solution was injected into the inner tube of the coaxial needle. The flow rates of the inner and outer tubes were set to 1:1, both 0.5 mL / min. The needle was 15 cm away from the roller bracket. The tubular bracket composed of composite nanofibers can be prepared by replacing receiving devices with different diameters. Here, the roller diameter is set to 2.0 cm for receiving electrospun fibers, and the roller speed is 2000 rpm. Under the action of high voltage (22.5 kV), the spinning solution is sprayed in the electric field to form fibers deposited on the receiver to form a fiber membrane. The electrospinning voltage and spinning speed are randomly adjusted according to the spinning situation. When the required thickness is reached (0.1 mm in this case), the aluminum foil and the fiber membrane are carefully peeled off from the roller surface. The morphology of the electrospun fibers was observed and photographed using a scanning electron microscope (SEM). Based on the obtained SEM image, the electrospun fiber scanning electron microscope image was converted into a grayscale image (8-bit, 2048x2048 pixels) 2D-FFT image, and then analyzed by image analysis software Image J and its plug-in Oval profile were processed and the orientation degree of the prepared nanofibers was analyzed and calculated, and the orientation degree was 0.116.
[0117] (3) Preparation of randomly oriented natural polysaccharide / nanofiber composite hydrogel: The modified gelatin prepared in step (1) was prepared into 50 mL of modified gelatin solution A with a concentration of 12% by weight by volume using ultrapure water; a photoinitiator Irgacure 2959 (CIBA Chemicals) was added to the modified gelatin solution A to obtain solution C, wherein the final concentration of Irgacure 2959 was 0.05% by weight by volume; solution C was composited with the randomly oriented nanofibers prepared in step (2) but not containing silk fibroin (the solution C was injected into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and the nanofibers were alternately placed during the process, with 3 nanofiber layers, and the upper and lower layers were solution C), and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, the solution C can also be printed by 3D systems ProX 800 and photocured during the printing process), thereby obtaining a randomly oriented natural polysaccharide / nanofiber composite hydrogel.
[0118] Comparative Example 3 Preparation method of randomly oriented silk fibroin / natural polysaccharide / nanofiber composite hydrogel
[0119] (1) Preparation of modified gelatin: The preparation method of modified gelatin is the same as that in Example 1.
[0120] (2) Preparation of randomly oriented composite nanofibers: Polycaprolactone (PCL), modified gelatin (MeGel) and silk fibroin were mixed in a mass ratio of 5:4:1 to obtain a mixture, and the mixture was dissolved in a mixed solvent system of hexafluoroisopropanol (HFIP) and 90 v / v% acetic acid (the mass ratio of HFIP to 90% acetic acid was 9:1) to prepare a 15 wt% PCL / SF / MeGel mixed spinning solution, and randomly oriented composite nanofibers were prepared by electrospinning technology, as shown in the following example. Bottom: The mixed spinning solution is sucked into a 2.5mL syringe (the pushing speed of the syringe is 0.5mL / h), the inner diameter of the metal needle of the syringe is 0.5mm, and the distance from the receiving plate is 15cm; under the action of high voltage (22.5kV), the spinning solution is sprayed in the electric field to form fibers deposited on the flat plate receiver to form a fiber membrane; when the required thickness is reached (0.1mm in this case), the aluminum foil and the fiber membrane are carefully peeled off from the roller surface; based on the obtained SEM image, the orientation degree is 0.108 according to the image analysis software Image J processing and calculation.
[0121] (3) Preparation of randomly oriented silk fibroin / natural polysaccharide / nanofiber composite hydrogel: The modified gelatin prepared in step (1) was prepared into 50 mL of modified gelatin solution A with a concentration of 12% by weight by volume using ultrapure water; a photoinitiator Irgacure 2959 (CIBA Chemicals) was added to the modified gelatin solution A to obtain solution C, wherein the final concentration of Irgacure 2959 was 0.05% by weight by volume; solution C was compounded with the randomly oriented composite nanofiber prepared in step (2) (solution C was injected into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and nanofibers were alternately placed during the process, with 3 nanofiber layers, and the upper and lower layers were solution C), and then placed under 365 nm ultraviolet light for photocuring for 5 min (when a specific shape is required, solution C can also be printed by 3D systems ProX 800 and photocured during the printing process), thereby obtaining a randomly oriented silk fibroin / natural polysaccharide / nanofiber composite hydrogel.
[0122] Comparative Example 4: Preparation method of a cell-carrying hydrogel
[0123] The preparation method of this comparative example is the same as that of comparative example 1, except that step (2) is:
[0124] (2) Preparation of cell-laden hydrogels:
[0125] All materials were sterilized under UV for more than 1 hour, the modified gelatin solution was dissolved in DMEM-F12 medium at a mass volume ratio of 10%, and a photoinitiator Irgacure 2959 (CIBA Chemicals) solution was added to obtain solution C, wherein the final concentration of Irgacure 2959 was 0.05% by mass volume ratio. 7 The amount of cells / mL solution C was 1.547 cells / mL, and human adipose-derived mesenchymal stem cells (HADMSC cells, Sigma) were inoculated into solution C to obtain solution E. Solution E was injected into a disc mold with a diameter of 20 mm and a thickness of 5 mm, and then placed under 365 nm ultraviolet light for photocuring for 5 min to obtain a cell-laden hydrogel.
[0126] Comparative Example 5 Preparation method of a cell-carrying randomly oriented natural polysaccharide / nanofiber composite hydrogel
[0127] The preparation method of this comparative example is the same as that of comparative example 2, except that step (3) is:
[0128] (3) Preparation of randomly oriented natural polysaccharide / nanofiber composite hydrogels loaded with cells: All materials were sterilized under ultraviolet light for more than 1 h, the modified gelatin prepared in step (1) was dissolved in DMEM-F12 culture medium at a mass volume ratio of 10%, and a photoinitiator Irgacure 2959 (CIBA Chemicals) solution was added to obtain solution D, wherein the final concentration of Irgacure 2959 was 0.05% by mass volume ratio. 7 The amount of cells / mL solution D was 100 μg / mL, and human adipose-derived mesenchymal stem cells (HADMSC cells, Sigma) were inoculated into solution D to obtain solution E. Solution E was injected into the upper and lower layers of a disc mold with a diameter of 8 mm and a thickness of 3 mm, 1 mm each, and the 0.1 mm randomly oriented nanofibers prepared in step (2) were added in the middle, and then placed under 365 nm ultraviolet light for photocuring for 5 min to obtain a cell-laden randomly oriented natural polysaccharide / nanofiber composite hydrogel.
[0129] Comparative Example 6 Preparation method of a cell-carrying silk fibroin / natural polysaccharide / nanofiber composite hydrogel
[0130] The preparation method of this comparative example is the same as that of comparative example 3, except that step (3) is:
[0131] (3) Preparation of randomly oriented silk fibroin / natural polysaccharide / nanofiber composite hydrogel loaded with cells: All materials were sterilized under ultraviolet light for more than 1 h, the modified gelatin prepared in step (1) was dissolved in DMEM-F12 culture medium at a mass volume ratio of 10%, and a photoinitiator Irgacure 2959 (CIBA Chemicals) solution was added to obtain solution D, wherein the final concentration of Irgacure 2959 was 0.05% by mass volume ratio. 7 The amount of cells / mL of solution D was 100 μg / mL, and human adipose-derived mesenchymal stem cells (HADMSC cells, Sigma) were inoculated into solution D to obtain solution E. Solution E was injected into the upper and lower layers of a disc mold with a diameter of 8 mm and a thickness of 3 mm, 1 mm each, and the 0.1 mm randomly oriented nanofibers prepared in step (2) were added in the middle, and then placed under 365 nm ultraviolet light for photocuring for 5 min to obtain a randomly oriented silk protein / natural polysaccharide / nanofiber composite hydrogel loaded with cells.
[0132] Effect Example
[0133] (1) The acellular hydrogels prepared in the above-mentioned comparative examples 1 to 3 and examples 1 to 3 were subjected to stress-strain tests using a dynamic thermomechanical analyzer through a compression model, and then the strain energy was calculated according to the formula σ=ce αε The strain energy is calculated. The strain energy calculation results are as follows Figure 1As shown: the strain energy of Examples 1 to 3 is much higher than that of Comparative Examples 1 to 3; indicating that adding silk fibroin and / or using core-shell nanofibers can increase the strain energy (mechanical properties) of the hydrogel, among which the strain energy increased by using core-shell nanofibers is significantly higher than that of adding silk fibroin.
[0134] (2) After the cell-laden hydrogels of Examples 4 to 6 and Comparative Examples 4 to 6 were cultured in DMEM F12 medium for 14 days, Runx2 gene and osteocalcin OCN gene were detected by qPCR. The detection steps were as follows:
[0135] ① Isolation and purification of RNA: Take a hydrogel disc (8mm in diameter, 3mm in thickness) after 14 days of culture, add 0.5mL TRIzol, crush, let stand for 5min, add 0.1mL chloroform, mix well and let stand for 2min, centrifuge at 12000rcf at 4℃ for 15min, transfer the upper aqueous phase RNA to a new centrifuge tube, add 0.5mL isopropanol containing glycogen blue, let stand for 10min after mixing, centrifuge at 10000rcf at 4℃ for 10min, remove the supernatant, add 0.7mL 75% ethanol, mix well and centrifuge at 7500rcf at 4℃ for 5min, remove the supernatant, add 0.7mL 75% ethanol, mix well and centrifuge at 7500rcf at 4℃ for 5min, remove the supernatant, add 20μL nuclease-free water after natural drying for 20min, tap, and use Nanodrop 2000 to detect purity;
[0136] ② Synthesize cDNA: prepare a reaction solution containing qScript, add the extracted RNA, and then complete the synthesis and cloning of cDNA on an Eppendorf Mastercycler device;
[0137] ③qPCR: Prepare the upstream and downstream primers of three genes, 18s, Runx2 and OCN, and the SYBR reaction solution, add the cDNA obtained in step ②, seal the membrane and centrifuge for 10 seconds, and complete the qPCR in Bio-rad CFX connect Real time system. The PCR reaction system used is as follows:
[0138] 6 μL of nuclease-free water, 1 μL of 10 μM upstream primer and 10 μM downstream primer, 10 μL of SYBR, and 2 μL of template cDNA (synthesized in step ②).
[0139] The PCR reaction conditions were as follows: denaturation at 95°C for 5 min; 30 cycles of 94°C for 45 s, 55°C for 45 s, and 72°C for 60 s; and extension at 72°C for 10 min.
[0140] 18s upstream primer: 5'-CCAACCTGGTTGATCCTGCCAGTA-3' (SEQ ID NO. 1);
[0141] 18s downstream primer: 5'-CCTTGTTAACGACTTCACCTTCCTCT-3' (SEQ ID NO. 2);
[0142] OCN upstream primer: 5'-GGCAGCGAGGTAGTGAAGA-3' (SEQ ID NO. 3);
[0143] OCN downstream primer: 5'-CCTGAAAGCCGATGTGGT-3' (SEQ ID NO. 4);
[0144] Runx2 upstream primer: 5′-CCTCCTACCTGAGCCAGATG-3′ (SEQ ID NO. 5);
[0145] Runx2 downstream primer: 5′-CCAGAGGCAGAAGTCAGAGG-3′ (SEQ ID NO. 6).
[0146] The results are as follows Figure 2 As shown: compared with the control group (comparative examples 4 to 6), after 14 days of culture, the expression levels of Runx2 gene and osteocalcin OCN gene in the embodiment group (examples 4 to 6) were significantly reduced, indicating that: the hydrogel provided by the present invention helps to inhibit osteogenic differentiation, that is, osteogenic differentiation can be inhibited by adding nanofibers.
[0147] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An anisotropic silk fibroin / gelatin / nanofiber composite hydrogel, consisting of S1 and S2: S1: an anisotropic core-shell nanofiber layer, the shell layer of the anisotropic core-shell nanofiber is a mixture M, the core layer of the anisotropic core-shell nanofiber is a synthetic polymer, and the mixture M is methacryloyl-modified gelatin and silk fibroin; S2: methacryloyl-modified gelatin layer containing functional substances; The synthetic polymer is polycaprolactone, polylactic acid, or polyethylene glycol; The functional substance is stem cells; The S1 and S2 are alternately stacked; The number of layers of S1 is n, the number of layers of S2 is n+1 or n-1; n is 2, 3, 4, 5, or 6; The preparation method of the anisotropic core-shell nanofiber is as follows: using a solution of the mixture M as a shell spinning solution and a solution of a synthetic polymer as a core spinning solution, coaxial electrospinning is performed to obtain anisotropic core-shell nanofibers; The concentration of the solution of the mixture M is 15-20wt%; The concentration of the synthetic polymer solution is 10-15wt%; The preparation method of the composite hydrogel comprises the following steps: mixing a functional substance, a photoinitiator and a methacryloyl-modified gelatin to obtain a mixture B; stacking the mixture B and anisotropic core-shell nanofibers, and photocuring the mixture to obtain an anisotropic silk fibroin / gelatin / nanofiber composite hydrogel comprising an S1 anisotropic core-shell nanofiber layer and a S2 methacryloyl-modified gelatin layer containing a functional substance; The photoinitiator comprises an Irgacure series photoinitiator; The photocuring method is to perform photocuring under ultraviolet light; and it is achieved by a 3D printer.
2. The hydrogel according to claim 1, characterized in that: The thickness of the anisotropic core-shell nanofiber layer is 0.1-1.3 mm.
3. The hydrogel according to claim 1, characterized in that: The steps of the coaxial electrospinning are as follows: placing the shell layer spinning solution and the core layer spinning solution in an injection device respectively, the propulsion speed of the shell layer spinning solution is 0.1-2 mL / h, the propulsion speed ratio of the shell layer spinning solution to the core layer spinning solution is 1:(0.5-1.5), the distance between the needle of the injection device and the receiving device is 8-25 cm, the rotation speed of the receiving device is 500-3500 rpm, and the spinning voltage is 10-30 kV.
4. Use of the anisotropic silk fibroin / gelatin / nanofiber composite hydrogel according to any one of claims 1 to 3 in the preparation of biomedical materials.
5. A biomedical material comprising the anisotropic silk fibroin / gelatin / nanofiber composite hydrogel according to any one of claims 1 to 3.
